Factors of Electricity Prices in Selected Eu Member States after the Financial Crisis and During Significant Market Distortions - Krizanic, France; Oplotnik, Zan Jan (International Journal of Energy Economics and Policy, 2017)
Analysis of the electric power market in a region of five EU countries (Austria, Croatia, Hungary, Italy and Slovenia) with one-sixth of the EU population reveals that in the period following the last financial crisis growth of 1% in electricity consumption led to 0.9% higher electric power prices for industry and 0.6% higher electricity prices for households. The situation on the German electricity market also holds a statistically significant influence. An increase in taxes in the German price of electricity (collected to raise funds intended for power generation from renewable sources) of 1% leads to 0.25% reduction in electricity prices for industrial use and 0.12% reduction in electricity prices for households in the analyzed group of EU Member States. From 2010 to 2015, Germany opened the subsidization of electricity generation from renewable sources from 12 to 24 billion euros per year (0.8% of GDP in 2015). This has had the impact of increasing the supply of electricity and providing only intermittent information about the actual cost of production of these goods. Between 2011 and 2015, the electric power price on the German Energy Exchange (Phelix) fell 38%. Keywords: Electricity Market, Electricity prices, Production of Electricity, Energy and the Economy JEL Classifications: D40, L94, Q43, F00